Evaluation of relaparotomy in surgery and obstetrics and gynecology patients in tertiary care hospital in India: reason, morbidity, mortality: a case controlled study - Shah, Pooja; Choksi, Dilip; R., Arun; Chauhan, Sahdev; Kadia, Ronak (International Surgery Journal, 2020)
Background: Many laparotomy may require relaparotomy due to post-operative complication as life-saving procedure. Incidence of relaparotomy and post-operative outcome defers from patient to patient. The objectives of our study were to evaluate the indication of relaparotomy, outcome of the relaparotomy and factors affecting mortality. Methods: Data was collected between March 2017 and November 2019 in SSG hospital, Vadodara. Patient’s demographics, indication and intra-operative findings of initial surgery and relaparotomy with morbidity and mortality were studied. Patients from department general surgery and obstetrics and gynecology were included. Consent was taken in a pre-validated form. Results: Out of total 5684 laparotomy performed, 146 (2.58%) patients underwent relaparotomy. Male to female ratio was 1.5:1. Incidence was highest in 31-40 years age group (median age: 37 years). Dirty wound in initial laparotomy had highest conversion rate (3.21%) to relaparotomy. Mean interval between initial laparotomy and relaparotomy was 8.57±5.62 days. The major indication of relaparotomy was burst abdomen (39.52%) followed by leak from previously sutured site (24.65%). 50.68% patients were shifted to ICU following relaparotomy. Average days of ICU admission were 4.16±2.25 days. Mortality rate was 23.29%. Maximum mortality was noted in case of leak from anastomotic or perforation site. 14 (38.88%) deaths occurred during postoperative day second to fourth with mean hospital stay of 21.85±8.65 days. Conclusions: Although relaparotomy is life-saving procedure, it has high mortality rate. The possibility of efficiently lowering relaparotomy depends on success of the first laparotomy, patient’s status, early re-exploration with proper surgical techniques and thorough postoperative care.